Associated factors with chronic complications of type-2-diabetes mellitus among patients from a general hospital of the Peruvian social health insurance - Villacorta Santamato, Juan (2020)
Introduction. The chronic complications of type-2-diabetes mellitus (T2DM) increase mortality and burden of disease in Peru, then it is necessary to evaluate its prevalence and associated factors. Methods. Cross-sectional study in records of 212 adult outpatients with T2DM attended by a social security general hospital in Peru, during 2017. Results. 71,6% of patients were older than 60 years and with a time of illness less than 6 years (40,5%). 38,7% of the patients had any chronic complication, mainly nephropathy (48,8%) and neuropathy (45,1%). Hypertension (52,4%) and obesity (43,7%) were the most frequent comorbidities in outpatients with chronic complications. Complications from DMT2 were associated with the medical consultations and glycemic monitoring. Conclusions. There are risk factors associated to chronic complications of DMT2.